The tale of Matsura : Fujiwara Teika's experiment in fiction - Fujiwara, Sadaie, 1162-1241; Lammers, Wayne P., 1951- (Michigan monograph series in Japanese studies, 1992)
Fujiwara Teika is known as the premier poet and literary scholar of the early 13th century. It is not so widely known that he also tried his hand at fiction: Mumyōzōshi (Untitled Leaves; ca. 1201) refers to "several works" by Teika and then names Matsura no miya monogatari (The Tale of Matsura; ca. 1190) as the only one that can be considered successful. The work is here translated in full, with annotation. Set in the pre-Nara period, The Tale of Matsura is the story of a young Japanese courtier, Ujitada, who is sent to China with an embassy and has a number of supernatural experiences while there. Affairs of the heart dominate The Tale of Matsura, as is standard for courtly tales. Several of its other features break the usual mold, however: its time and setting; the military episode that would seem to belong instead in a war tale; scenes depicting the sovereign's daily audiences, in which formal court business is conducted; a substantial degree of specificity in referring to things Chinese; a heavy reliance on fantastic and supernatural elements; an obvious effort to avoid imitating The Tale of Genji as other late-Heian tales had done; and a most inventive ending. The discussion in the introduction briefly touches upon each of these features, and then focuses at some length on how characteristics associated with the poetic ideal of yōen inform the tale. Evidence relating to the date and authorship of the tale is explored in two appendixes.